CT and CEST MRI bimodal imaging of the intratumoral distribution of iodinated liposomes - Chen, Zelong; Li, Yuguo; Airan, Raag; Han, Zheng; Xu, Jiadi; Chan, Kannie W. Y.; Xu, Yikai; Bulte, Jeff W. M.; van Zijl, Peter C. M.; McMahon, Michael T.; Zhou, Shibin; Liu, Guanshu (Quantitative Imaging in Medicine and Surgery; Vol 9, No 9 (September 25, 2019): Quantitative Imaging in Medicine and Surgery, 2019)
Background: To develop liposomes loaded with iodinated agents as nanosized CT/MRI bimodal contrast agents for monitoring liposome-mediated drug delivery. Methods: Rhodamine-labeled iodixanol (VisipaqueTM)-loaded liposomes (IX-lipo) were prepared and tested for their properties as a diamagnetic CEST contrast agent in vitro. Mice bearing subcutaneous CT26 colon tumors were injected i.v. with 1 g/kg (535 mg iodine/kg) IX-lipo, and in vivo CT and CEST MR images were acquired on day 3. CT and CEST MR images were also acquired for tumor-bearing mice co-injected with IX-lipo and tumor necrosis factor (TNF-α). Results: In addition to CT contrast, IX-lipo exhibited a strong CEST contrast similar to its non-liposomal form, with a detectability of ~2 nM per liposome. Both CT imaging and CEST MRI showed that i.v. injection of IX-lipo resulted in a rim enhancement of CT26 tumors with a heterogeneous central distribution. In contrast, co-injection of TNF-α caused a significantly augmented CT/MRI contrast in the tumor center. The intratumoral biodistribution of IX-lipo correlated well to the rhodamine patterns observed with fluorescence microscopy. Conclusions: We have developed a CT/MRI bimodal imaging approach for monitoring the delivery and biodistribution of liposomes by loading them with the clinically approved X-ray/CT contrast agent iodixanol. Our approach may be easily adapted for other-FDA approved iodinated agents and thus has great translational potential.